2009
DOI: 10.1242/dev.030577
|View full text |Cite
|
Sign up to set email alerts
|

Disc1 regulatesfoxd3andsox10expression, affecting neural crest migration and differentiation

Abstract: This work reports the characterization and functional analysis of disrupted in schizophrenia 1 (disc1), a well-documented schizophrenia-susceptibility gene, in zebrafish cranial neural crest (CNC). Our data demonstrated that disc1 was expressed in zebrafish CNC cells. Loss of Disc1 resulted in persistent CNC cell medial migration, dorsal to the developing neural epithelium, and hindered migration away from the region dorsal to the neural rod. General CNC cell motility was not affected by Disc1 knockdown, howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 69 publications
3
68
1
Order By: Relevance
“…SOX9 acts specifically in craniofacial development, downstream of the WNT and bone morphogenic protein (BMP) pathways , and it has been found [Shao and Vawter, 2008;Chen et al, 2013;Lanz et al, 2013]. SOX10 regulates the NC stem cell balance during development; it is functionally related to the SZ susceptibility gene DISC1 during early NC cell migration [Drerup et al, 2009] and oligodendrocyte differentiation [Hattori et al, 2014]. SOX10 is found to be hypermethylated in the brain of SZ patients [Iwamoto et al, 2005] and carries singlenucleotide polymorphisms that have been related to the age of onset of clinical manifestations [Yuan et al, 2013].…”
Section: Functional Implication and Biological Interpretation Of Domementioning
confidence: 99%
See 1 more Smart Citation
“…SOX9 acts specifically in craniofacial development, downstream of the WNT and bone morphogenic protein (BMP) pathways , and it has been found [Shao and Vawter, 2008;Chen et al, 2013;Lanz et al, 2013]. SOX10 regulates the NC stem cell balance during development; it is functionally related to the SZ susceptibility gene DISC1 during early NC cell migration [Drerup et al, 2009] and oligodendrocyte differentiation [Hattori et al, 2014]. SOX10 is found to be hypermethylated in the brain of SZ patients [Iwamoto et al, 2005] and carries singlenucleotide polymorphisms that have been related to the age of onset of clinical manifestations [Yuan et al, 2013].…”
Section: Functional Implication and Biological Interpretation Of Domementioning
confidence: 99%
“…functional status may have occurred during recent human evolution. FOXD3 is also a transcriptional target of the SZ candidate DISC1 , and it is involved in cranial NC migration and differentiation [Drerup et al, 2009]. SOX9 and SOX10 indirectly interact through FOXD3 , as shown in Figure 3 , being coexpressed at different stages of NC development.…”
Section: Functional Implication and Biological Interpretation Of Domementioning
confidence: 99%
“…Sox10 expression is markedly reduced in both Foxd3 mutant embryos (Teng et al, 2008) and NC cultures. Although it is possible that Foxd3 may regulate Sox10 expression and vice versa, it is also likely that they are coordinately regulated (Drerup et al, 2009). Sox10 preservation of glial fates may act in synchrony with Foxd3-mediated maintenance of neural competency within NCSCs to ensure multipotency.…”
Section: Molecular Regulation Of Progenitor Cell Multipotency and Selmentioning
confidence: 99%
“…Subsequent genetic studies have confirmed that the DISC locus is involved in multiple psychiatric disorders and cognitive function, in several populations worldwide (Chubb et al, 2008;Jaaro-Peled, 2009). Efforts to model DISC1 disease biology in transgenic mice, and more recently in Drosophila and zebrafish, have been quite successful (Sawamura et al, 2008;Wang et al, 2008;Drerup et al, 2009;Kellendonk et al, 2009). In general DISC1 mutant mice, from a range of approaches, show behavioral and anatomical deficits that can be linked to psychiatric disease.…”
Section: Introductionmentioning
confidence: 99%